O046 Association of sleep characteristics with low muscle strength: the Hypnolaus cohort study. (7th October 2021) - Piovezan, R; Yu, S; Hirotsu, C; Marques-Vidal, P; Visvanathan, R; Heinzer, R
Abstract: Background: Muscle deterioration is a hallmark of aging and sleep may play a role in the development of sarcopenia. Population-based studies including objective evaluation of sleep characteristics and disorders may provide evidence of how sleep affects muscle function across adulthood. We aimed to evaluate associations of sleep characteristics with handgrip strength in a population-based cohort study. Methods: Participants of the HypnoLaus study (Lausanne, Switzerland) aged >40 years were cross-sectionally evaluated through questionnaires and PSG. Muscle strength was assessed by hand dynamometer and low muscle strength (LMS) was defined according to the criteria for sarcopenia (<27 kg for men, <16 kg for women). Multivariate logistic regression analysis controlling for potential confounders wereapplied. Results: 1902 participants (mean [SD] age, 57.4 [10.5] years; 968 [50.9%] female) were enrolled. LMS was detected in 95 (5.0%) participants. After controlling for sociodemographic characteristics, lifestyle factors, and comorbidities, objectively measured long sleep duration (>8h) was independently associated with LMS (OR=2.41, 95%CI=1.36–4.27). Subjective measures of sleep duration and quality, excessive daytime sleepiness, and other sleep characteristics obtained by PSG were not associated with LMS. Conclusions: Objectively measured long sleep duration rather than short sleep duration was associated with LMS in a population-based study including participants aged >40 years. Self-reported sleep duration was not associated with LMS. The findings suggest long sleep duration measured by PSG is a potential risk factor for sarcopenia and should be considered as a target in preventive and therapeutic strategies against the development of muscle health decline observed with aging.